The common marmoset as an indispensable animal model for immunotherapy development in multiple sclerosis. Issue 8 (August 2016) - Kap, Yolanda S.; Jagessar, S. Anwar; Dunham, Jordon; 't Hart, Bert A.
Highlights: We developed a valid preclinical model for chronic MS in marmosets. The model displays pathological aspects of progressive MS in cortical grey matter. The model shows a central role of an EBV-homologue in the progressive phase. Abstract : New drugs often fail in the translation from the rodent experimental autoimmune encephalomyelitis (EAE) model to human multiple sclerosis (MS). Here, we present the marmoset EAE model as an indispensable model for translational research into MS. The genetic heterogeneity of this species and lifelong exposure to chronic latent infections and environmental pathogens create a human-like immune system. Unique to this model is the presence of the pathological hallmark of progressive MS, in particular cortical grey matter lesions. Another great possibility of this model is systemic and longitudinal immune profiling, whereas in humans and mice immune profiling is usually performed in a single compartment (i.e. blood or spleen, respectively). Overall, the marmoset model provides unique opportunities for systemic drug–effect profiling.